Problems about the Legal Status of The Administrative Pre–Contract - Numnoi, Panlapa (Naresuan University Law Journal, 2014)
According to the research about the legal status of the administrative pre–contract in the governmental procurement cases the author attempts to support the concept that the administrative pre–contract is a kind of contract to be accepted. In case where the legal status of administrative precontractual agreement is identified as an innominate contract (unnamed contract), it produces clear advantages in terms of dispute adjudication. This means the disputes arising from the legal status of administrative pre–contractual agreement will be reduced since such status will depend on a principal contract. Moreover, the proof of damages will be easier since liquidated damages will be determined in case where there is a breach of contract. This is obviously different from the proof of actual damages in torts. And when we could separate the administrative pre–contract which is an administrative contract from the civil contract, we could make the unity proceeding to be occurred.